Common Voice Disorders among Bus Helpers in Dhaka City (IAHS Medical Journal, 2024)
Background: There are approximately 9911 buses and 8515 minibuses are running within Dhaka city. Most of them have bus helpers who most of the time uses loud voice and yelling for their job. For which they are under a great risk of having voice disorder. No study was conduct to find the rate of voice disorder in this group. This study will seek out the rate of voice disorder and the risk among this group.Materials and methods: A total of 80 bus helpers participated in the study. Their vehicle routes were within Dhaka city. It was a cross-sectional survey. Sampling was done by convenience technique. Samples were selected from different bus depots in Dhaka city. Data were collected by face to face interview using a questionnaire. Data analysis was done by descriptive statistical analysis. Statistical Package for Social Science- 17 (SPSS) and Microsoft Excel 2007 were used for data analysis.Results: The result shows that 84% of bus helpers had voice problem throughout their carrier. Current symptoms present among them are hoarseness (92%) vocal fatigue (73%), pain in throat (58%), constant throat dryness (67%) and frequent throat clearing (48%). Less frequent symptoms are breathy voice, strained voice, monotone voice, sore throat, acid taste and loss of voice. Only risk factor found is not drinking adequate water.Conclusion: The study reveals that different types of Vocal disorders are very common among the bus helpers. So, preventive measures and education are necessary to get rid of this problem.IAHS Medical Journal Vol 7(1), June 2024; 60-64